KEEFEKTIFAN MULTIMEDIA BERBASIS STORYTELLING TERHADAP HASIL BELAJAR SISWA PADA MATERI KEBERAGAMAN BUDAYA KEDIRI DI KELAS IV SDN KEREP - Maecha Kusuma Wardani; Dhian Dwi Nur Wenda; Farida Nurlaila Zunaidah (Jurnal Manajemen Pendidikan, 2026)
This research and development aims to determine the effectiveness of storytelling-based multimedia on Kediri cultural diversity material in grade IV of SDN Kerep. The method applied in this research is the research and development method (Research and Development). In this study, the ADDIE development model is used as an approach to design products in the form of storytelling-based learning multimedia developed through structured stages. The material used focuses on the theme of diversity in the Kediri region for grade IV students. In the limited trial stage, it was carried out in grade IV with 8 students as respondents, while in the extensive trial it was carried out in grade IV with 17 students as respondents. The data analysis techniques used are qualitative and quantitative descriptive analysis. The results of this study show the effectiveness of storytelling-based multimedia on Kediri cultural diversity material in grade IV of SDN Kerep. The effectiveness of the media can be seen from the increase in student learning outcomes, where the pretest score of 71% increased to 89% in the posttest. From the results of these scores, storytelling-based learning multimedia on Kediri cultural local wisdom received a very effective assessment to be used as a learning medium for cultural diversity material, especially Kediri cultural local wisdom in grade IV of Elementary School.